Analysis of Differences Between Hospital Rates and INA-CBG's Claim of Sectio Caesarea - Hayati, Afriliya; Budi, Savitri Citra; Dani, Ika Aria (Universitas Muhammadiyah Sidoarjo, 2024)
Hospitals as advanced referral facilities have an important role in implementing the National Health Insurance (JKN) programme. For payment of advanced health services for JKN participants at the hospital, BPJS makes payments based on the Indonesian case-based groups (INA-CBG's) package. However, the problem that is often found in hospitals is the difference between hospital rates and INA-CBG's claim. This study aims to determine and analyse the difference between hospital rates and INA-CBG's claim for sectio caesarea cases at Bhayangkara Polda DIY Hospital. This study was a descriptive quantitative study with a retrospective approach. The object of the study was the BPJS patient's inpatient claim file for sectio caesarea cases at Bhayangkara Polda DIY Hospital in the fourth quarter of 2023. The number of samples was 39 patients using the total sampling technique. The results showed a significant difference (p< 0,05) between hospital rates and INA-CBG’s claim for sectio caesarea cases at Bhayangkara Polda DIY Hospital. The difference between hospital rates and INA-CBG’s claim caused a negative difference of Rp.10,865,028,00. There is a negative difference between the hospital rates and the INA-CBG's claim for sectio caesarea cases at Bhayangkara Polda DIY Hospital, so the hospital suffers a loss.